Examination of the impact and consequences of the COVID-19 pandemic on mental health - Petrović, Bojana; Vukomanović, Predrag; Nikolić, Milica (Archives of Pharmacy, 2022)
The ongoing Coronavirus disease 2019 (COVID-19) pandemic poses a serious threat to public health worldwide. Moreover, COVID-19 pandemic has also led to the mental health consequences due to the financial and existential uncertainties and social constraints. The study was conducted from February to May 2021 to determine the impact of the COVID-19 pandemic on an individual’s mental health. A total of 104 volunteers (62 female and 42 male) participated in the study, of whom close to 60% suffered from COVID-19, as well as close to 90% of their family members. In addition, 10% of respondents report the death of a family member as the outcome of COVID-19, which coincides with the official reports of the Institute of Public Health "Dr Milan Jovanovic Batut" of the Republic of Serbia. The DASS-21 scale was used to assess the degree of anxiety, stress, and depression, as well as mental health in general. The results indicate the highest degree of stress (in 52.9% of respondents), while anxiety disorders and depression are present in more than a third of respondents (about 35%). Similar results were obtained in an Italian study, which confirms the need for a timely response and empowerment of the individual to seek professional help. These data were especially emphasized in the respondents who reported a death within the family. The results of our study, as well as numerous other studies, unequivocally indicate the negative impact of the COVID-19 pandemic on mental health. Furthermore, potential psychopathological consequences have yet to be thoroughly investigated.